Multi-Energy Acquisition Modeling and Control Strategy of Underwater Vehicles - Shen, Shijun; Wang, Chaofan; Qiu, Zhiqiang; Ke, Zhiwu; Gong, Dawei (Frontiers in Energy Research, 2022)
There are two types of underwater robots: wired and unwired. The unwired underwater robot(AUV), which can only carry limited energy, not only improves its flexibility, but also brings the problem of working endurance. The acquisition of environmental energy by underwater robot is a positive way to supplement the energy and increase the endurance. However, the instability and the difference of power output capacity of different environmental energy will lead to the low utilization of environmental energy. In this paper, a multi-energy acquisition model is established according to the AUV’s motion mode and environment. And it designs a heart rate sampling system, a mixed energy circuit topology, and a maximum power output algorithm of environmental energy based on the power trajectory tracking. The simulating results show that the power output control strategy can effectively improve the multi-energy acquisition and utilization efficiency of the underwater vehicles, which has positive significance to improve its endurance time.